The Process of Execution of Fiduciary Guarantees Seized as Evidence because the Debtor Committed a Criminal Act (Case Analysis of Decision Number 188/Pdt.Bth/2019/PN.Dpk) - Fitriana, Desy Nor; Aisy, Nisrina Nadifah Nur Rohadhatul; Aisy, Azkia Rihadatul; Astuti, Windha Puji (Diponegoro Private Law Review, 2021)
The abstract should be in one paragraph.The font is Book Antiqua, 12 pt, italic, and justify. Abstract is in 200-250 words, which is followed by 3-5 keywords. The abstract should succinctly describes your entire paper. It comprises of the purposes of the research, method, and the findings of the research. Provision of credit from banks and financial institutions will definitely be risky if the debtor defaults, to overcome this the borrower in providing credit must be accompanied by providing guarantees for the debtor. The purpose of the guarantee is to guarantee security and legal certainty for investors in granting credit. In a credit agreement, creditors often expect guarantees that provide a sense of security and trust. Even though a fiduciary guarantee has a guarantee, it is not certain that a problem will not occur. Problems with basic agreements such as credit with a fiduciary guarantee can generally arise because the fiduciary recipient or creditor only forms a credit agreement, can also occur because the party only forms a notary deed by not registering it with the office that administers the fiduciary guarantee. There are still many problems that arise as the author will analyze, namely problems with the execution of objects that are used as guarantees for fiduciary acessoir agreements, where the objects are confiscated by the state because of criminal acts committed by the fiduciary giver or debtor. In this case, through a lawsuit at the Depok District Court, the fiduciary recipient can execute objects pledged as objects of fiduciary guarantees previously in the possession of the Depok District Attorney as evidence of a crime.Keywords: Fiduciary, Collateral, Credit